2016
DOI: 10.1007/s10493-016-0081-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of the tick-borne pathogen Anaplasma marginale in cattle blood samples from Nigeria using qPCR

Abstract: Tick-borne diseases (TBDs) are some of the most important animal health and management problems in Africa, including Nigeria. This study aims to determine the prevalence of an important TBD, anaplasmosis, in a North-central region of Nigeria. Blood samples were collected from cattle and stored on Whatman FTA cards. Information on village, age and sex associated with each cattle was also recorded. The packed red blood cell volume (PCV) for each blood sample was determined. After DNA extraction, pathogen presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The overall infection rate with A. marginale described in our study was 11.1%. Several studies detecting A. marginale infection in cattle have been carried out in some regions from Africa with different rates such as in Tunisia (25.4%) (Belkahia et al., ); Morocco (21.9%) (Ait Hamou et al., ); Sudan (6.1%) (Awad et al., ); Egypt (3.7%) (Younis, Hegazy, El‐Deeb, & El‐Khatib, ); Madagascar (89.7%) (Pothmann et al., ); Nigeria (75.9%) (Elelu, Ferrolho, Couto, Domingos, & Eisler, ); Kenya (32.5%) (Adjou Moumouni et al., ); Angola (38%) (Kubelová, Mazancová, & Siroky, ); and Mozambique (67%) (Machado et al., ). This is the case also in Turkey (2.3%) (Aktas et al., ), Brazil (5.4%) (Silva et al., ), Pakistan (17%) (Ashraf et al., ) and Mongolia (8.7%) (Ybañez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The overall infection rate with A. marginale described in our study was 11.1%. Several studies detecting A. marginale infection in cattle have been carried out in some regions from Africa with different rates such as in Tunisia (25.4%) (Belkahia et al., ); Morocco (21.9%) (Ait Hamou et al., ); Sudan (6.1%) (Awad et al., ); Egypt (3.7%) (Younis, Hegazy, El‐Deeb, & El‐Khatib, ); Madagascar (89.7%) (Pothmann et al., ); Nigeria (75.9%) (Elelu, Ferrolho, Couto, Domingos, & Eisler, ); Kenya (32.5%) (Adjou Moumouni et al., ); Angola (38%) (Kubelová, Mazancová, & Siroky, ); and Mozambique (67%) (Machado et al., ). This is the case also in Turkey (2.3%) (Aktas et al., ), Brazil (5.4%) (Silva et al., ), Pakistan (17%) (Ashraf et al., ) and Mongolia (8.7%) (Ybañez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for low detection rates in ticks and hosts is the existence of a second parasite co-infection (Purnell et al 1977;Friedhoff 1990;Kocan 1995;Zintl et al 2003). Elelu et al (2016) sampled the same individuals included in this study and found 75.9% to be positive for Anaplasma marginale. Within the definitive host, it has been suggested, through experimental infection of splenectomised calves, that concurrent infection with Anaplasma is able to supress Babesia colonisation (Purnell et al 1977;Zintl et al 2003).…”
Section: Resultsmentioning
confidence: 76%
“…The animals were randomly selected and clinically healthy at sampling. The procedures for sample selection, collection, extraction and storage can be found in Elelu et al (2016). From the 253 samples collected, 96 were excluded from the current study due to a lack of sufficient biological material.…”
Section: Study Populationmentioning
confidence: 99%
“…It is estimated that three-quarters of the world's dog population live as village or community dogs and only a few kept as pets (Coppinger and Coppinger, 2001). In tropical and subtropical regions of the world, vector-borne diseases commonly occur in various species of animals (Irwin and Jefferies, 2004;Elelu et al, 2016). Globally, dogs have been documented to be infected by different haemoparasites such as bacteria, viruses and eukaryotic parasites, which are transmitted through different arthropod vectors such as ticks and mosquitoes causing huge morbidity and mortality (Otranto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%